Islamization of science & technology: theory and reality - Asar, Abdul Karim (2010)
Islamization of knowledge has been the concern of Muslim intellectuals all over the world. It has been generalized to all contemporary knowledge including science and technology {S & T). History shows that the process of Islamization has taken place since the time of the prophet Muhammad SAW and continued by various Muslim scholars and sages from the early centuries of Islam until now. This concept was widely discussed mainly after the monograph of ai-FarDqT entitled "Islamization of Knowledge: General Principles and Workplan" in 1982. The concept triggered two perceptions: supporting and opposing views from scholars. The concept claimed to be able to help Muslims face existing challenges, rediscover the essence of Islam and recapture the past glory days. The fact that intrigued the researcher was all the writings that came to his attention were written in unclear about lslamizing science and technology; prevailing the existing arguments. In this paper, the researcher tries to conclude what exactly the Islamization of S & T should be; is it to lslamize the knowledge or to give some principles or guidelines for S & T. In addition to this, the backwardness of Muslim world is not only caused by the so-called secular knowledge, but also it rather goes back to internal and external problems. Moreover, the influence of un-lslamic Western culture, acts as one of the main factors that prevent Muslims to achieve the Islamization of knowledge particularly, Islamization inS & T.